The Effects of Feeding Benzoic Acid and Essential Oils on Sows and Litter Performance - M. T. Thayer; J. L. Nelssen; A. Langemeier; J. Morton; Z. Ou; J. R. Bergstrom (Kansas Agricultural Experiment Station Research Reports, 2017)
A total of 48 sows (DNA Line 200 × 400) and their progeny were used in this study to determine if feeding sows and/or piglets benzoic acid (VevoVitall, DSM Nutritional Products, Parsippany, NJ) paired with an essential oil blend (CRINA, DSM Nutritional Products, Parsippany, NJ) enhances sow and pig performance during lactation, piglet weight gain in the nursery, and survivability to market. For sow and preweaned piglet performance in the farrowing house, adding benzoic acid and an essential oil blend to the maternal diet did not affect (P>0.05) litter performance or weaning weight of the piglets. Fecal swabbing litters the day before weaning showed the pigs did not eat the creep feed. Nursery pigs weighed on d 12 or d 45 postweaning were not heavier (P>0.05) due to the maternal diet or the presence/absence of creep feed in the farrowing crate. Also, survivability of pigs from weaning to market did not increase due to maternal diet (P>0.05). From this study, it appears that benzoic acid paired with an essential oil blend does not affect sow and pig performance or survivability to market.
Keywords: benzoic acid; essential oils; sows; creep feed